Tectonomagmatic setting of lava packages in the Mandla lobe of the eastern Deccan volcanic province, India: palaeomagnetism and magnetostratigraphic evidence - Pathak, Vamdev; Patil, S.K.; Shrivastava, J.P. (2016)
Flow-by-flow palaeomagnetic measurements of 37 lava flows in the 900 m-thick, isolated lava pile around Mandla in the eastern Deccan Volcanic Province (DVP) reveals multiple magnetic polarity events: implying C29n–C28r–C28n magnetostratigraphy. Magnetic polarity results when traced out from section to section, maintaining the order of superposition, show juxtaposition of lava packages with distinct characters near Deori (e.g. flows 1–4 abated against flows 5–14) and the Dindori areas. At Dindori and towards its south, the distinct lava packages (e.g. flows 15–27 and flows 28–37) are juxtaposed along the course of Narmada river. It is explained by the presence of four normal post-Deccan faults in the Nagapahar, Kundam–Deori, Dindori and Badargarh– Amarkantak sectors: thus, signifying structural complexity with vertical shifts or offset of 150–300 m. Magnetic chron reversals in conjunction with field and chemical data support these findings. Further, these lavas are compositionally akin to Bushe, Poladpur, Ambenali and Mahableshwar Formational lavas, and follow the same stratigraphic order as in the Western Ghats. Alternating field (AFD) and thermal demagnetizations (THD) isolate the normal mean direction of the Mandla lobe: D ¼ 344.58 and I ¼ 2308, where D and I are the mean declination and inclination of the each lava flow (a95 ¼ 8.2; K ¼ 72.6; N ¼ 17, where a95 is the half-angle of the cone of 95% confidence about the mean direction, K is the precision parameter and N is the number of flows). The Virtual Geomagnetic Pole (VGP) position determined for these lavas, when compared with the Deccan Super Pole, indicates concordance with the main Deccan volcanic province, thus assigning a shorter period of eruption close to the Cretaceous–Palaeogene boundary (K/PB) for the eastern and western Deccan Traps.